ANALISIS PEMASARAN TOMAT DIDESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Made Antara, Abdul Muis, Rizka. M (AGROTEKBIS, 2015)
This report aims to review the marketing tomatoes and large margin marketing obtained marketing each institution in every - for the marketing, knows part of prices received by farmers ( producers ) in every for marketing channel tomatoes, knows efficiency marketing tomatoes in the village labuan toposo in labuan.This research carried out in villages labuan toposo in labuan sub district donggala.Get as 30 respondents 50 farmers in a random sample of simple ( simple random sampling ).In addition, determine respondents traders used method of poll respondents ( tracing sampling ) with, take trader as many as 2 people and traders as many as the retailer 2.The total cost as much as 34 respondents.The results of the analysis showed that the total the margin marketing tomato obtained to channel first Rp 1,000 and total the margin marketing tomato obtained to channel both the Rp 2,000.Part the prices received by farmers of the i of 60 % and parts of the prices received by farmers of the ii of 66,67 %.Thus, part the price the greatest received by farmers is on channels two.Marketing outlets tomatoes origin village labuan toposo there are two channel viz: (1) farmers intermediary traders a retailer consumers.(2) farmers traders a retailer consumers.The first the efficiency of the to intermediary traders of 7,23 %, and traders a retailer of 11,12 % and channel score efisinsinya of 9,20 %.Of two channels marketing the tomatoes, marketing outlets efficient is a conduit second.